1999
DOI: 10.1016/s1388-1981(99)00158-4
|View full text |Cite
|
Sign up to set email alerts
|

PAF-acetylhydrolases

Abstract: Platelet-activating factor acetylhydrolases (PAF-AHs, EC 3.1.1.47) constitute a unique subfamily of phospholipases A(2), specific for short acyl chains in the sn-2 position of the phospholipid. Their primary substrate is the platelet-activating factor, PAF, from which they cleave an acetyl moiety with concomitant release of lysoPAF. However, some acetylhydrolase will also hydrolyze other polar phospholipids with up to 6-carbons long acyl chains in the sn-2 position. PAF-acetylhydrolases are diverse enzymes, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
3

Year Published

2003
2003
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 23 publications
0
18
0
3
Order By: Relevance
“…The mechanism of ester hydrolysis suggests that the backbone amides of F274, immediately downstream of the catalytic serine (S273), and L153 form part of the oxyanion hole and stabilize tetrahedral intermediates generated during catalysis. In addition, residues 189-239 inserted at the carboxyl edge of the central β sheet have been proposed to define substrate specificity and lipoprotein binding [16]. Interestingly, we found that Y205 was required for binding of PAF-AH to LDL, and this residue is Fig.…”
Section: Structure Of Paf-ahmentioning
confidence: 75%
See 1 more Smart Citation
“…The mechanism of ester hydrolysis suggests that the backbone amides of F274, immediately downstream of the catalytic serine (S273), and L153 form part of the oxyanion hole and stabilize tetrahedral intermediates generated during catalysis. In addition, residues 189-239 inserted at the carboxyl edge of the central β sheet have been proposed to define substrate specificity and lipoprotein binding [16]. Interestingly, we found that Y205 was required for binding of PAF-AH to LDL, and this residue is Fig.…”
Section: Structure Of Paf-ahmentioning
confidence: 75%
“…Interestingly, we found that Y205 was required for binding of PAF-AH to LDL, and this residue is Fig. 2 Tertiary fold of PAF-AH based on previous models by Wei et al [15] and Derewenda and Ho [16] and modified to include newly discovered domains. Catalytic triad residues (S273, D296 and H351) and two residues that confer susceptibility to oxidation (Y305 and Y335) lie within loops proposed to connect helical and β sheet domains.…”
Section: Structure Of Paf-ahmentioning
confidence: 99%
“…The biochemistry and biological functions of the major cPLA 2 s (groups IV and VI) and acetyl hydrolases (groups VII and VIII) have been reviewed elsewhere [17, 18, 19, 20]. …”
Section: Introductionmentioning
confidence: 99%
“…Here, M. persicae chitinase matched with an acetylhydrolase found in A. pisum and platelet-activating factor acetylhydrolase (PAF hydrolase) from Drosophila, Aedes and Culex species. This kind of acetylhydrolase constitutes a subfamily of phospholipase specific for acyl chains [9]. The related phospholipids are key components of biological membranes and are the source of signaling molecules involved in many regulatory pathways associated with different physiological functions [8].…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, M. persicae chitinase appeared to be different from other insect chitinases. Hypothesis on the change of functional constraints were developed to explain the divergences in insect chitinases [9]. The match between M. persicae chitinase, an endochitinase and a Concanavalin B suggests that it belongs to chitinases from family 18 such as previous insect chitinases studied so far that all have been shown to possess signature motifs characteristic of family 18 glycosyl hydrolases [2].…”
Section: Discussionmentioning
confidence: 99%